Pesan-pesan Dakwah dalam Bahasa Tutur - Hikmat, Hikmat (Jurnal Ilmu Dakwah, 2011)
Forwarding of The daâwah messagesÂ  in oral language. Oral language in this context isÂ  transmitted, trasacted and transformated from relevan values. Even if the message of daâwah in oral language is culture frame that eksist in community, but its posite not outsideÂ  of principles: qulan sadidan, Balighan, maârufan, kariman, layyinan, dab qoulan maysuran, that the message od daâwah can be manual by people danÂ  followed it, because daâI is a availableÂ  person for people followed it all.